R graphics - Murrell, Paul (Boca Raton CRC Press, 2019)
"This is the third edition of a very successful book on using R for graphics by one of the leaders in the field. This is a major update, with a complete overhaul in focus and scope. It will now focus primarily on the two core graphics packages in R - graphics and grid - and has a new section on integrating graphics. This section includes two new chapters on combining graphics systems and web graphics. The section on other graphics packages has been removed, with discussion of some of these packages integrated with other parts of the book, where appropriate. The book will remain the key reference for the core graphics systems in R"--
An introduction to R graphics -- Simple usage of base graphics -- Customizing base graphics -- Trellis graphics : the lattice package -- The grammar of graphics : the ggplot2 package -- The grid graphics model -- Developing new graphical functions and objects -- Graphics formats -- Graphical parameters -- Importing graphics -- Combining graphics systems -- Advanced graphics.
Includes bibliographical references and index.
Keywords: Computer graphics; R (Computer program language)